2008
DOI: 10.2164/jandrol.107.004416
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Estradiol and Free T4 Are Inversely Correlated With Sperm DNA Damage in Men From an Infertility Clinic

Abstract: Sperm DNA damage adversely affects male fertility and contributes to poorer embryo development and lower pregnancy rates. Endogenous hormones are critical to spermatogenesis and maintenance of male reproductive function and likely play an important role in human sperm DNA integrity, but this relationship is not fully understood. The present study measured serum hormone levels and sperm DNA damage with the neutral comet assay in 362 male partners of infertile couples. When sperm concentration and other potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 62 publications
2
23
1
Order By: Relevance
“…6 Despite the lack of correlation (r < 0.1) we recently reported between TPHP concentrations in house dust and DPHP concentrations in urine, 7 in the present study we found that urinary DPHP was associated with decreased sperm concentration and increased serum prolactin (though the association with prolactin was confounded by time of day of sample collection since prolactin levels are also higher in samples collected in the afternoon 20 ) in patterns consistent with our previous report on house dust concentrations of TPHP. 6 Although peculiar, there may be several possible explanations for consistent relationships between these endpoints and two exposure assessment approaches that were not correlated with one another: 1) the significant results for either house dust or urinary biomarker concentrations (or both) are due to chance findings; 2) Both TPHP and DPHP are bioactive, and there may be other uses (e.g., as a plasticizer) and sources of DPHP besides TPHP in house dust, 21 thus both measures may be associated with the same outcome measure but not with each other; 3) DPHP may be a metabolite of other chemicals in addition to TPHP (e.g., certain alkylated triphenyl phosphate isomers used as flame retardants, among others 22 ) that may be associated with these endpoints; 4) Since TPHP exposure may come from sources or locations outside the home (e.g., offices, automobiles), perhaps the two measures reflect differing aspects of exposure and both were associated with substantial but differing error in relation to true exposure.…”
Section: Discussioncontrasting
confidence: 70%
“…6 Despite the lack of correlation (r < 0.1) we recently reported between TPHP concentrations in house dust and DPHP concentrations in urine, 7 in the present study we found that urinary DPHP was associated with decreased sperm concentration and increased serum prolactin (though the association with prolactin was confounded by time of day of sample collection since prolactin levels are also higher in samples collected in the afternoon 20 ) in patterns consistent with our previous report on house dust concentrations of TPHP. 6 Although peculiar, there may be several possible explanations for consistent relationships between these endpoints and two exposure assessment approaches that were not correlated with one another: 1) the significant results for either house dust or urinary biomarker concentrations (or both) are due to chance findings; 2) Both TPHP and DPHP are bioactive, and there may be other uses (e.g., as a plasticizer) and sources of DPHP besides TPHP in house dust, 21 thus both measures may be associated with the same outcome measure but not with each other; 3) DPHP may be a metabolite of other chemicals in addition to TPHP (e.g., certain alkylated triphenyl phosphate isomers used as flame retardants, among others 22 ) that may be associated with these endpoints; 4) Since TPHP exposure may come from sources or locations outside the home (e.g., offices, automobiles), perhaps the two measures reflect differing aspects of exposure and both were associated with substantial but differing error in relation to true exposure.…”
Section: Discussioncontrasting
confidence: 70%
“…In agreement, both antiestrogens and aromatase inhibitors have been reported to interfere with SPT elongation [46,47]. Furthermore, recent epidemiological studies showed that the serum concentrations of either estrogen and free thyroxine (T4) or estrogen and testosterone inversely correlated with sperm DNA damage in men [48,49].…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, estrogens, directly or indirectly, affected SPZ chromatin acting on the testis rather than epididymis, since histone-to-protamine exchange takes place during spermiogenesis Overall, our results demonstrated that estrogens, indirectly via stimulatory effects on FSH secretion and/or directly via paracrine actions within the testis, play a key role in spermiogenesis. Interestingly, it is still a matter of debate whether FSH and/or estrogen affect chromatin remodeling in SPT in either a synergistic or an independent way with androgens [42,49,58,71,72]. However, the loss of Cnr1 did not impair fertility [15]: this likely occurs because of mechanisms of SPZ selection (Cnr1 À/À mice produce a sperm with heterogeneous histone content and chromatin quality) and/ or DNA repair operating in the female reproductive tract [73].…”
Section: Estrogens and Spermatid Chromatin Packagingmentioning
confidence: 99%
“…Intact sperm chromatin and sperm maturity are important for the reproductive potential of men [Meeker et al 2008]. Sperm chromatin damage negatively affects fertility potential and it may result in poor embryo quality with low pregnancy rates [Agarwal et al 2004; Lewis and Aitken 2005;Morris et al 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Sperm chromatin damage may resolve as: i) oxidative stress (OS), ii) poor chromatin packaging or abnormal packing due to defective protamination, iii) abortive apoptosis, and iv) impairment in recombination during spermatogenesis resulting in cell apoptosis [Agarwal and Said 2003;Erenpreiss et al 2006;Sakkas et al 1999]. The most widely reported causes are OS, sperm nuclear protamination, and serum hormones [Appasamy et al 2007;Meeker et al 2008].…”
Section: Introductionmentioning
confidence: 99%